Real-World Clinical Characteristics and Outcomes with Daptomycin Use in Pediatric Patients: A Retrospective Case Series - Hanna Persha; Stephen A. Thacker; Krutika Mediwala Hornback; Gustavo R. Alvira-Arill; Richard Lueking; Taylor Morrisette (MDPI AG, 2024)
Introduction: Daptomycin (DAP) is a cyclic lipopeptide that exhibits potent in vitro activity against many drug-resistant gram-positive organisms, including methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE). Despite substantial reports evaluating the clinical outcomes of DAP within the adult population, real-world data are lacking in children. The primary goal of this evaluation was to describe the clinical characteristics and outcomes of DAP use in pediatric patients across a wide range of infections. Methods: This retrospective evaluation included patients < 18 years of age who were treated with DAP from January 2014 to May 2023. The primary objective was to evaluate the composite clinical success, which was defined as a 30-day survival, the lack of a 30-day microbiological recurrence, and the resolution of signs and symptoms of an acute infection without therapy modifications based on clinical failures. Secondary objectives included adverse effects potentially attributable to DAP and reasons for DAP utilization. Results: Forty patients were included, which were predominately male (62.5%) and white (52.5%), with a median age of 8.7 [IQR, 4.4-16.0] years. DAP was used for a wide range of infections, including central line-associated bloodstream infections (CLABSIs; 32.5%), infective endocarditis (15.0%), surgical-site infections (12.5%), and osteomyelitis (12.5%). The most common pathogen isolated was MRSA (37.5%), and most patients were bacteremic (60.0%). The median DAP dose was 8 [IQR, 6-10] mg/kg, and the median duration of the DAP therapy was 11.5 [IQR, 4.8-18.8] days. Most patients achieved composite clinical success (75.0%). An adverse effect occurred in 5.0% of the patients. DAP was prescribed the most for its ease of use/ability to facilitate discharge (40.0%) and/or for issues with alternative therapies (37.5%). Conclusion: Most pediatric patients that received DAP demonstrated clinical success with a low incidence of adverse effects. Larger, real-world studies of DAP use are necessary to further assess clinical outcomes.